Proteasome limits plasticity-related signaling to the nucleus in the hippocampus - Vashisht, Anirudh (Neurosci Lett, 2018)
Proteolysis by the ubiquitin-proteasome pathway has pleiotropic effects on both induction and maintenance of long-term synaptic plasticity. In this study, we examined the effect of proteasome inhibition on signaling to the nucleus during late-phase long-term potentiation. When a subthreshold L-LTP induction protocol was used, proteasome inhibition led to a significant increase in phosphorylated CREB (pCREB) in the nucleus. Inhibitors of cAMP-dependent protein kinase/protein kinase A, extracellular signal-regulated kinase and cGMP-dependent protein kinase/protein kinase G all blocked the proteasome-inhibition-mediated increase in nuclear pCREB after subthreshold stimulation. These results lay the groundwork for understanding a novel role for the proteasome in limiting signaling to the nucleus in the absence of adequate synaptic stimulation.